Effect of Gender on Morphological Awareness and Reading Comprehension Competence in Chinese Language: Evidence from the University of Cape Coast - Opoku-Darko, James; Nkrumah, Bright (American Journal of Education and Practice, 2022)
Purpose: There are evidences that students studying Chinese language in Ghana find it difficult to read and form simple Chinese words using the HÃ nyÇ” PÄ«nyÄ«n system. Nevertheless, little is known of how gender influences morphological awareness and reading comprehension in Chinese language, as well as the relationship between morphological awareness and reading comprehension. This study, thus, using a correlational research design, examined whether there is any difference between male and female students with respect to morphological awareness and reading comprehension, and the relationship between morphological awareness and reading comprehension. Methodology: Employing the census sampling technique, a sample of 100 BA Chinese students at the University of Cape Coast was involved in the study. Morphological awareness and reading comprehension tests were used to collect data from the participants. Data were analyzed using means, standard deviations, two independent samples t-test and the Pearson correlation coefficient. Findings: The results showed that there were no significant differences between male and female BA Chinese students in terms of morphological awareness and reading comprehension. It was further revealed that morphological awareness is positively associated with reading comprehension in Chinese language. It was, thus, concluded that improved awareness of morphology would enhance reading comprehension competence of BA Chinese students at the University of Cape Coast. Recommendation: It was suggested that the Ministry of Education Ghana introduce Chinese language studies into the basic and high school education systems in Ghana to ensure pre-exposure of students to the language before they enter institutions of higher education.